2022
DOI: 10.1186/s12885-022-09945-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for rebleeding and long-term outcomes in patients with head and neck cancer bleeding: a multicenter study

Abstract: Background Acute, catastrophic bleeding in patients with head and neck cancer (HNC) is challenging and also a burden for their families and frontline physicians. This study analyzed the risk factors for rebleeding and long-term outcomes in these patients with HNC. Methods Patients who presented to the emergency department (ED) with HNC bleeding were enrolled in this study (N = 231). Variables of patients with or without rebleeding were compared, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Second, all significant variables from the univariable analyses were inputted into the multivariable logistic regression model to further examine their statistical association. Continuous variables were categorized as a priori using either the standard threshold values established in our laboratory settings or thresholds associated with poor outcomes, as identified in the existing literature [17][18][19][20][21][22][23][24]. In the multivariable model, a p-value of < 0.05 was set as the threshold for the incorporation of variables into the final prediction score.…”
Section: Derivation Stagementioning
confidence: 99%
“…Second, all significant variables from the univariable analyses were inputted into the multivariable logistic regression model to further examine their statistical association. Continuous variables were categorized as a priori using either the standard threshold values established in our laboratory settings or thresholds associated with poor outcomes, as identified in the existing literature [17][18][19][20][21][22][23][24]. In the multivariable model, a p-value of < 0.05 was set as the threshold for the incorporation of variables into the final prediction score.…”
Section: Derivation Stagementioning
confidence: 99%
“…Poor intake due to dysphagia, odynophagia, and esophageal stenosis can lead to malnutrition and cachexia, which might weaken the immune system and reduce the resistance to infection. Additionally, previous research suggested that patients with nutritional deficiency might have poorer tolerance to the toxicity of chemoradiotherapy and surgical intervention (37)(38)(39).…”
Section: B Amentioning
confidence: 99%
“…Wang et al 85 analyzed 231 patients with head and neck cancer who experienced bleeding. Among these patients, 112 (48.5%) had a recurrent bleeding event.…”
Section: New Risk Factors For Bleeding In Patients With Cancermentioning
confidence: 99%